The Cyanamide Moiety, Synthesis and Reactivity - Larraufie, Marie-Hélène; Maestri, Giovanni; Malacria, Max; Ollivier, Cyril; Fensterbank, Louis; Lacôte, Emmanuel (Synthesis, 2012)
The cyanamide moiety provides many opportunities as a building block for the synthesis of nitrogen-containing heterocycles. This review discusses the reported methods for the preparation of alkyl- and N-acylcyanamides and illustrates their reactivity vis-à-vis nucleophilic additions, cycloadditions, radical chemistry and coordination chemistry.1 Introduction2 Biological Relevance of the Cyanamide Moiety3 Access to Cyanamides3.1 Cyanation of Amines3.2 Palladium Catalysis3.3 Deoxygenation of Isocyanates3.4 Desulfurization of Thioureas4 Reactivity of Cyanamides4.1 Nucleophilic Additions4.2 Cycloadditions4.3 Additions to Carbonyl Groups4.4 Chlorinations and Oxidations with tert-Butyl-N-chlorocyanamide4.5 Cyanamides as Radical Partners5 Coordination Chemistry of Cyanamides6 Conclusion
Keywords: cyanamide; cyanation; nitrogen; heterocycles; nitrogen ligands